Variability of average consumption of cold and hot water per resident in a multi-apartment residential buildings - Szaflik, Władysław (Instal, 2021)
The article presents the method of determining the probability of the average daily total and hot water consumption based on the number of residents in multi-apartment buildings. It has been assumed that the average daily water consumption by a single resident of a building is a random variable with a normal distribution of the expected value –qj and standard deviation S–qj . Using these assumptions the distribution parameters were determined. For the purpose of the study, the results of measurements of the average annual water consumption in 2019 from sixty-five buildings located in Szczecin were obtained. Knowledge of the distribution parameters makes it possible to determine the variation of unit consumption values according to probability. The average water consumption per resident was calculated for probability levels of 90%, 95% and 99% in relation to the number of residents. The obtained results were compared on graphs.
Keywords: water supply systems; water consumption; unit hot and cold water intake